Optical properties of n-type asymmetric triple ?-doped quantum well under external fields (2020)
We present a theoretical investigation about the the influence of external electric, magnetic and non-resonant intense laser fields on intersubband-related second harmonics generation (SHG) and the nonlinear optical rectification (NOR) coefficients in n-type asymmetric triple ?-doped quantum wells (QWs). A particular design of asymmetric triple ?-doped QW with L w = 200 Å width and, respectively, in the left side, central and right side, and doping concentrations is taken into account. For QWs under the combined effect of the external electric, magnetic and laser fields, the time-dependent wave equation is modified by using Kramers-Henneberger transformation and the dipole approximation. The subband energy spectra and the electronic wave functions are obtained by solving numerically the wave equation. The originality of this work can be presented as; (i) The results explain NOR and SHG characteristics of triple QW depending on external field effects in detail. The effects of the electric, magnetic and laser field on transition energies and NOR, SHG characteristics are presented detail. (ii) In addition to, the alternativeness to each other of the external fields is discussed by probing the features of SHG and NOR under the strong and weak regimes of external fields. (iii) These nonlinear optical responses to the external fields are compared, researching the optimum cases for these optical specifications. (iv) The control of SHG through the external fields in triple ?-doped QWs reveals to be easier and more precise. © 2020 IOP Publishing Ltd.